Search for neutral-current induced single photon production at the ND280 near detector in T2K. (20th June 2019) - Abe, K; Akutsu, R; Ali, A; Andreopoulos, C; Anthony, L; Antonova, M; Aoki, S; Ariga, A; Ashida, Y; Awataguchi, Y; Azuma, Y; Ban, S; et al.
Abstract: Neutrino neutral-current (NC) induced single photon production is a sub-leading order process for accelerator-based neutrino beam experiments including T2K. It is, however, an important process to understand because it is a background for electron (anti)neutrino appearance oscillation experiments. Here, we performed the first search of this process below 1 GeV using the fine-grained detector at the T2K ND280 off-axis near detector. By reconstructing single photon kinematics from electron–positron pairs, we achieved 95% pure gamma ray sample from 5.738 × 10 20 protons-on-targets neutrino mode data. We do not find positive evidence of NC induced single photon production in this sample. We set the model-dependent upper limit on the cross-section for this process, at 0.114 × 10 − 38 cm 2 (90% C.L.) per nucleon, using the J-PARC off-axis neutrino beam with an average energy of E ν ∼ 0.6 GeV. This is the first limit on this process below 1 GeV which is important for current and future oscillation experiments looking for electron neutrino appearance oscillation signals.